Innervated Bilobed Radial Forearm Free Flap For Tongue Reconstruction - Atmodiwirjo, Parintosa; Bangun, Kristaninta; Handayani, Siti; Djamaloeddin, Chaula; Nindita, Eliza (Jurnal Plastik Rekonstruksi, 2012)
Hemiglossectomy defects need reconstructions to restore normal functions and aesthetic outcomes. It is therefore prudent that well-planned reconstructive technique is needed for a good functional substitution for the defect.This case report describes a 30 years old male who developed T2N1M0 squamous cell carcinoma of the left tongue. The patient underwent a tongue reconstruction following his hemiglossectomy involving floor of the mouth without mandibular resection.The optimum method of reconstructing a major defect such as hemiglossectomy with floor of the mouth resection is best carried out by using microvascular free tissue transfer.  We conclude that the radial forearm free flap is good method for reconstructing major defects of the tongue. The radial forearm free flap is thin, can be raised without patient position change, has constant vascular anatomy, and provides an advantage in the aesthetic aspect at the donor site.